The Role of Legal Politics in Creating Legal Reform in Increasing Foreign Investment in Indonesia - Dameria Kristina Pardede (Strata Law Review, 2023)
Investment is currently regulated in the Job Creation Law. Still, previously, investment regulations were contained in Law Number 25 of 2007 concerning Capital Investment, whereas Law Number 25 of 2007 reflected that investment regulations had two sides. One side of investment will open up state income and so on. Meanwhile, on the other hand, by opening up investment opportunities, various facilities and conveniences will be offered to investors in order to attract investment interest in a country. This research aims to analyze the Ciptaker Law as a regulation that amends the Investment Law using a participatory paradigm so as to provide analysis regarding investment regulations in Indonesia. This research is a type of normative legal research that bases its approach on legislation and conceptualization. The results of this research conclude that the Job Creation Law related to investment aims to adjust various regulatory aspects related to improving the investment ecosystem, facilitating and accelerating national strategic projects oriented towards national interests based on national science and technology guided by Pancasila ideology. Regarding these conditions, foreign investment can provide legal protection and legal certainty based on established law.